How Implementing of Social Capital to Improving Islamic Education Quality: The Social Evolution Model - Awang Saputra; Ahmad Sutarmadi; Saiful Bahri; Sanusi Uwes (Indonesian Journal of Social Research (IJSR), 2022)
Social change is a phenomenon that often occurs in life that demands improvement and creates shared prosperity to strengthen social capital as a component involved in it. The low average formal education in Indonesia is still low in Southeast Asia, which gives the impression that most Muslims do not have adequate quality education because there are still many people who are socially marginalized. The number of graduates of Islamic education itself is low. They make men more dignified by utilizing resources to create new things and have a wider impact. Islam has described social capital and social change in life as necessary to create a more dynamic value of life. This study is to find out how social capital is implemented by social capital to improve the quality of education with a social evolution approach. The method uses qualitative research using a grounded theory approach and analytical design thinking. The results show that come contents of social capital as a component of change that can improve the quality of Islamic education, including trust, networks, norms, and leadership, which are built on six models of social evolution, namely empathy, exploration, elaboration, exposure, and execution and expansion. The social evolution model built on design thinking can formulate efforts to improve the quality of Islamic education through strengthening the social capital formed. Research implies that improving Islamic education can be adapted to social changes in social modal, specifically in the human resources index.